Harnessing technopreneurial mindset and social innovation: A framework for Industry 5.0 - Muhammed, Jawo; Fernando, Yudi; Wijayanti, Risna (Emerald Publishing, 2025)
Purpose: This study examines the intersection of the technopreneurial mindset, social innovation and Industry 5.0. This study aims to develop a unified framework that supports a responsible, human-centric industrial transformation. Although existing literature on Industry 5.0 has predominantly focused on technological advancement, there has been limited attention given to integrating entrepreneurial and social innovation dimensions that drive sustainable business ecosystems. Design/methodology/approach: A systematic literature review and bibliometric analysis were used to examine thematic trends and structural gaps across 533 academic publications. The study identifies key publication patterns, co-occurrence networks and conceptual clusters relevant to innovativon, sustainability and technopreneurship.Findings: The analysis reveals that the discourse surrounding Industry 5.0 is heavily centred on technology, with underdeveloped linkages to entrepreneurial and social innovation constructs. In response to this, the study proposes a conceptual framework comprising three interdependent components: technological foundations, social impact assessment and entrepreneurial strategies alignment. These dimensions are supported by thematic clusters that reflect the evolving dynamics of digital transformation, ethical innovation and societal well-being. Originality/value: This study makes a theoretical contribution by integrating underrepresented constructs into Industry 5.0 scholarship, thereby advancing a multidimensional framework that accounts for both technological capabilities and human-centric values. From a practical lens, the proposed framework offers strategic guidance for technopreneurs, innovation policymakers and scholars navigating the complex interplay between industrial development and inclusive innovation.